Do anthropometric and aerobic parameters predict a professional career for adolescent skiers? - Windhaber, J.; Steinbauer, M.; Castellani, C.; Singer, G.; Till, H.; Schober, P. (International Journal of Sports Medicine, 2019)
The aim of this study was to evaluate whether spiroergometry performance in adolescent alpine ski racers can predict later advancement to a professional career. Over 10 consecutive years, adolescent skiers of the regional Austrian Youth Skier Squad (local level) underwent annual medical examinations, including exhaustive bicycle spiroergometry. The performance was determined at fixed (2 and 4?mmol/l serum lactate) and individual (individual anaerobic threshold (IAT) and lactate equivalent (LAE)) thresholds. Data from the last available test were compared between skiers who later advanced to the professional level (Austrian national ski team) and those who did not. Ninety-seven alpine skiers (n=51 male; n=46 female); mean age 16.6 years (range 15-18) were included. Of these, 18 adolescents (n=10 male; n=8 female) entered a professional career. No significant differences were found for maximum oxygen uptake (VO2max). Athletes advancing to the professional level had significantly higher performance and VO2 at LAE. Additionally, male professionals had significantly higher performances at fixed thresholds and the IAT. The performance and VO2 at the LAE, and thus the ability to produce power at a particular metabolic threshold, was the most relevant spiroergometric parameter to predict a later professional career.